Motif Sosio-Theogenetis dalam Tradisi Manakiban Masyarakat Mejobo Kudus - Rahmawati, Ulfah (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2019)
Manaqiban is one of the activities that manifested in religious values practice. This article aims to illustrate that the manaqiban which exist in Mejobo, Kudus, Indonesia community are not only performed exclusively by those who gain the degree of excellence (ijazah) but also it has become a decline of the society. Through the qualitative method with the analytical descriptive approach and based on the motive theory and motif classification study, it is considered biogenetic, sociogenetic and theogenetic motifs, the results show that peoples influenced by sociogenetic and theogenetic motifs. Carrying on any traditions because of what the society and their families have done as sociogenetic motives, while theogenetic motives are seen on washilah prayer or tawashul to receive the blessing of Shaykh Abdul Qadir al-Jailani. The implications of the Mejobo peoples are in the individual organizers of the desire to seek safety, peace of mind and their religious beliefs.